Hart Crane - Fisher, Clive, 1960- (JSTOR EBA., 2002)
"Hart Crane's life was notoriously turbulent, persistently nonconformist, and tragically short. Born in 1899, Crane became one of the most significant modernist American poets, yet his self-destructive tendencies-violent outbursts, massive drinking binges, and dangerous sexual pursuits-came to a catastrophic conclusion when at only thirty-two he threw himself from the stern of an ocean liner into the Gulf of Mexico. This new biography presents for the first time a full, frank portrait of the real Hart Crane, a poet attractive both for his flamboyance and passion for life, and for the magnificent sonorities of his work.Clive Fisher mines every extant document left behind by Crane to recount the intertwined stories of the poet's life: his work and the intellectual climate in which he wrote, his urgent and intractable relations with his parents, and his tortured yet incessant quest for emotional stability and love. The book considers the autobiographical application of Crane's poems and recreates settings in London, Paris, Cleveland, Cuba, and Mexico where the poet found inspiration. Fisher redresses injustices to the reputation of Crane's father, Clarence; reintroduces Crane's important friends and their achievements; and without the constraints that hindered previous biographers presents Crane's promiscuity, positioning his activities in the context of the New York gay underworld of his time. The book also takes up the suicidal tendencies of Grace Crane, Hart's mother, and recreates the scene of the poet's death with fresh material from documents of those aboard the ship. This absorbing biography at last provides an authoritative portrait of Hart Crane, a poet whose remarkable work places him among the most important American writers of the twentieth century."--Publisher.